Understanding sample product quality, purchase decision, and brand awareness of Nescafe - Kiswara, Adimas Rangga (Review of Management, Accounting, and Business Studies, 2024)
This study explored the impact of sample product quality and brand awareness on consumer purchasing decisions for Nescafe coffee products in Denpasar, Indonesia, during the COVID-19 pandemic and under the Indonesian government’s Large-Scale Social Restrictions (PSBB). These restrictions limited traditional marketing channels, including direct consumer interactions that were essential to Nescafe’s sampling strategy, which historically relied on face-to-face engagement to boost brand recognition and trust. The research focused on how sample quality and brand awareness influenced consumer decisions and examined whether brand awareness mediated the relationship between sample product quality and purchase intent. Using path analysis on data collected from 100 purposively sampled respondents, the study found that higher sample product quality directly improved both brand awareness and purchasing decisions. Additionally, brand awareness significantly enhanced the likelihood of a purchase and served as a mediating factor, strengthening the effect of sample product quality on purchase decisions. These findings underscored the value of high-quality sampling in building brand familiarity and consumer trust, especially when traditional marketing channels were constrained. The study suggested that brands could maintain consumer engagement and drive purchasing behavior by investing in quality-controlled sampling programs and developing robust brand awareness strategies, offering practical implications for marketing in challenging environments.